PENDEKATAN MEANINGFUL DALAM PEMBELAJARAN SEJARAH DI SEKOLAH BERBASIS BOARDING SCHOOL SMA PLUS ASTHA HANNAS - Tumarjio, Astin Eka; Abdu, Muhamad (Program Magister Pendidikan IPS UPY, 2025)
Abstract This study aims to look at meaningful learning activities in history subjects at Astha Hannas Plus High School which is dormitory-based. The approach used in this research is qualitative with descriptive method. Data collection techniques include interviews and observations. The results showed that Astha Hannas Plus High School has successfully integrated the concept of meaningful learning in learning activities. This application includes inductive and deductive approaches, which help students connect new information with their prior knowledge. In addition, character and moral values are taught and implemented in students' daily lives, creating a conducive and character development-oriented learning environment. Keywords: Meaningful Learning, History Learning, Boarding School